Alterações cardiovasculares induzidas pelo aumento da ingestão de sal ou de sacarose - Moreira, Marina Conceição dos Santos (2017)
Cardiovascular diseases (CVD) and their complications are the main causes of death around the world nowadays. Among these diseases, the hypertension stands out because of its great prevalence and multifactorial characteristic. Several studies demonstrate that, among other factors, the increased intake of industrialized food (rich in both salt and sugar) contribute to the pathophysiology of salt-dependent hypertension and obesity-related hypertension. However, the high sucrose intake induced cardiovascular modifications still need to be clarified. Based on these information, we sought to evaluate the effects of high salt intake of different durations during the post-natal period and of high sucrose intake in adulthood on cardiovascular parameters in adult animals. The present study sought to determine the cardiovascular and autonomic effects of salt and sucrose overload in adult animals. We evaluated the mean arterial pressure (MAP), the heart rate (HR) and the baroreflex sensitivity of the animals submitted to salt overload after weaning and to sucrose overload in adulthood and the cardiac morphology and Rostral Ventrolateral Medulla (RVLM) sensitivity after salt overload. 21 days old male Wistar rats received hypertonic saline solution (NaCl 0,3M) for 30 or 60 days (experimental groups). The control groups were maintained with tap water for equivalent period. After the treatment, the groups were maintained with tap water and food for 15 days (recovery period). A distinct group of adult animals was submitted to sucrose overload for 30 days. At the end of the experimental protocols, the animals were chronically cannulated. 24h after the surgery, the basal cardiovascular parameters and its modifications induced by baroreflex/chemoreflex stimulation were recorded. The baroreflex index was calculated as the ratio between HR and MAP changes after each infusion of phenylephyne and sodium nitroprusside. There were no differences between baseline MAP and HR of the animals treated during 30 days compared to the age-matched control animals (cont.: 118.2 ± 3.7 mmHg vs. exp.: 112.3 ± 4.0 mmHg; cont.: 404.0 ± 10.6 bpm vs. exp.: 374.7 ± 9.1 bpm). However, these animals presented diminished baroreflex sensitivity compared to the control group (BI: cont.; -2.441 ± 0.359 bpm/mmHg vs. exp.: -1.434 ± 0.086 bpm/mmHg, p<0.05). The animals submitted to high salt intake for 60 days after weaning presented increased MAP (cont. 98.6 ± 2.6 mmHg vs. exp. 117.7 ± 4.2 mmHg; p<0.05) and HR (cont. 365.4 ± 12.2 bpm vs. exp. 392.5 ± 10.3 bpm; p<0.05) compared to their control group. Moreover, the baroreflex sensitivity was diminished in those animals (cont. -1.83 ± 0.04 bpm/mmHg vs. exp. -1.24 ± 0.19 bpm/mmHg; p<0.05). The type I collagen relative frequency increased in the hearts of adult animals after 60 days after salt overload (cont.: 15.74 ± 0.61% vs. exp.: 19.79 ± 1.26%; p<0.05) but no differences were observed in the cardiomyocyte cross-sectional area. Furthermore, the pressure response to glutamate nanoinjections into the RVLM was increased in the animals treated for 60 days compared to the control group (cont.: Δ15.47 ± 2.56 mmHg vs. exp.: Δ34.31 ± 4.65 mmHg; p<0.05). The sucrose-treated animals presented increased MAP and HR compared to the control group (cont.: 102.5 ± 1.4 mmHg vs. exp.: 111.3 ± 0.9 mmHg; cont.: 334.7 ± 7.3 bpm vs. exp.: 371.6 ± 4.7 bpm; p<0.05). Furthermore, they presented diminished hypotension-induced baroreflex sensitivity (cont.: 5.0 ± 0.1 bpm/mmHg vs. exp.: 4.0 ± 0.1 bpm/mmHg; p<0.05) and increased pressure response after chemoreflex stimulation (cont.: 14.9 ± 1.9 mmHg vs. exp.: 29.2 ± 5.5 mmHg; p<0.05). Our results allow us to conclude that changes in the reflex regulation of blood pressure induced by salt overload after weaning precede the cardiovascular effects induced by such protocol, indicating that baroreflex sensitivity modifications can occur independently on permanent blood pressure changes. Moreover, salt overload after weaning promotes increases in RVLM sensitivity in adult animals. Furthermore, sucrose overload promotes MAP, HR and chemoreflex sensitivity elevation, whereas it promotes diminish of baroreflex sensitivity in adult rats. Taken together, our results allow us to conclude that changes in salt or sucrose intake produce permanent modifications in the arterial pressure control and such modifications are, in part, induced by changes in neuronal regulation of blood circulation.